Expression of Functional Cannabinoid CB(2) Receptor in VTA Dopamine Neurons in Rats - Zhang, Hai-Ying (Addict Biol, 2016)
We have recently reported the expression of functional cannabinoid CB(2) receptors (CB(2)Rs) in midbrain dopamine (DA) neurons in mice. However, little is known whether CB(2)Rs are similarly expressed in rat brain since significant species differences in CB(2) receptor structures and expression are found. In situ hybridization and immunohistochemical assays detected CB(2) gene and receptors in DA neurons of the ventral tegmental area (VTA), which was up-regulated in cocaine self-administration rats. Electrophysiological studies demonstrated that activation of CB(2)Rs by JWH133 inhibited VTA DA neuronal firing in single dissociated neurons. Systemic administration of JWH133 failed to alter, while local administration of JWH133 into the nucleus accumbens inhibited cocaine-enhanced extracellular DA and intravenous cocaine self-administration. This effect was blocked by AM630, a selective CB(2) receptor antagonist. These data suggest that CB(2)Rs are expressed in VTA DA neurons and functionally modulate DA neuronal activities and cocaine self-administration behavior in rats.